The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1039/d1cc02415a
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced homolytic decarboxylative acylation/cyclization of unactivated alkenes with α-keto acid under external oxidant and photocatalyst free conditions: access to quinazolinone derivatives

Abstract: A novel and green strategy for the synthesis of acylated quinazolinone derivatives via photo-induced decarboxylative cascade radical acylation/cyclization of quinazolinone bearing unactivated alkenes has been developed. The protocol provides a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…Notably, we found that the amount of cyclohexane has a remarkable effect on the yield, which might be related to the solubility of the starting materials. The yield did not increase markedly when the amount of cyclohexane was raised to 0.5 mL, whereas a cliff-like drop in yield when cyclohexane was reduced to 0.1 mL (entries [10][11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, we found that the amount of cyclohexane has a remarkable effect on the yield, which might be related to the solubility of the starting materials. The yield did not increase markedly when the amount of cyclohexane was raised to 0.5 mL, whereas a cliff-like drop in yield when cyclohexane was reduced to 0.1 mL (entries [10][11].…”
Section: Resultsmentioning
confidence: 99%
“…have independently constructed a series of polycyclic quinazolinones through direct C-2 alkylation of alkene substituted quinazolinones. [11] Nonetheless, to the best of our knowledge, in this strategy, the synthesis of polycyclic quinazolinones via C(sp 3 )À H functionalization of inert alkanes or visible-light promoted oxidation decarboxylation of N-hydroxyphthalimide (NHP)-esters has not been reported yet. As part of our continuous studies on the radical cyclization in green systems, [12] herein we describe the C(sp 3 )À H functionalization of inert alkanes or visible-light promoted oxidation decarboxylation of NHP-esters to form alkyl radicals, which then efficiently synthesize valuable polycyclic quinazolinones via radical cyclization of alkene substituted quinazolinones (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, Jin et al also reported a green strategy for the synthesis of acylated quinazolinone derivatives via the photo-induced decarboxylative cascade radical acylation/cyclization of quinazolinone containing unactivated alkenes 15 with α-oxo carboxylic acids 16 (Scheme 9). 15 This is the first example of the homolysis of the C–C bond of α-keto acids to form acyl radicals via a self-induced energy transfer (EnT) process. The reaction proceeded smoothly without any external photocatalyst, additive, or oxidant under a 395–400 nm light source.…”
Section: Difunctionalization Of Alkenes To Prepare 23-fused Quinazoli...mentioning
confidence: 99%
“…[48] In this sense, Sun and co-workers described a metal-and oxidant-free photoinduced reaction between quinazolin-4(3H)ones 55 bearing an alkene moiety and 2-oxo-phenylacetic acids 56 for the synthesis of dihydropyrrolo[2,1-b]quinazolin-9(1H)ones 57. [49] This reaction proceeds through decarboxylation and formation of acyl radical, followed by intramolecular cyclization and hydrogen atom abstraction, affording the desired products with moderated to good yields (Scheme 30). The reaction was also performed with sunlight irradiation in batch and under continuous flow regime and, in both cases, the products were obtained with comparable yields.…”
Section: Photoredox Reactionsmentioning
confidence: 99%